STUDY ON RATE AND SOME RELATED FACTORS TO HIGH BLOOD PRESSURE IN A PERSON FROM 40 YEARS AND OLDER IN BA VI DISTRICT HANOI CITY 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the prevalence and some factors related to hypertension in people aged 40years and older in Ba Vi district, Hanoi city, in 2023.Methods: A cross-sectional descriptive study with analysis was carried out through clinicalexamination and face-to-face interviews with 400 people aged 40 years and older to determine therate and some factors related to hypertension.Results: The rate of hypertension in the study subjects (Blood Pressure from 140/90mmHg or higher)was 36.75%. The number of people with normal blood pressure was 63.25%. The rate of hypertensionin the 61-70 age group was 38.78%, 51-60 age group was 26.53%, 41-50 age group was 19.05%. Therate of hypertension in men was 40.85% (87/213), and in women was 32.09% (60/187). Some factorsrelated to hypertension have been identified, including People’s knowledge about hypertension OR= 3.6, 95% CI: 2.362-5,570, p
Keywords: Hypertension, Ba Vi district.